Mortality from Infections Associated with Health Care in Patients with HIV in Paraguay - Lopez, Gladys; Aguilar, Gloria; Rios-González, Carlos Miguel (Medicina Clínica y Social, 2024)
Introduction: Few studies have evaluated HAIs in an HIV population; however, studies have suggested that patients with HIV are at a higher risk of contracting HAI because they have high rates of hospitalization and longer hospital stays. Objective: To determine mortality due to Infections Associated with Health Care in Patients with HIV in Paraguay from January to December 2018 to 2021. Methodology: This was an observational, descriptive, and cross-sectional study. The study population consisted of people over 18 years of age who died with a diagnosis of HIV infection and IAAS of both sexes during that period. The study variables were demographic, HIV-related, Baseline Viral Load, Stage of HIV infection at the time of diagnosis, Time from HIV diagnosis to death (in months), comorbidities at the time of death, microorganism isolation, presence, and location. of IAAS. Results: 93 patients with IAAS were included in the study, of which 34.4% (32) were between 20 and 29 years of age and 19.3% (18). Regarding the type of population, 79.3% (73) were in the general population, 77.6% (59) were diagnosed with AIDS, and 68.6% (59) had a baseline CD4 count of less than 200 cells/mm3. The mortality rate in 2020 was 6.7%, during 2018 it was 6.5% and in 2021 it and 6.4%. Conclusion: People with HIV, especially those who have been diagnosed in advanced stages of the disease, are more likely to develop HAIs and are related to mortality. This is due to the presence of multiple opportunistic infections and comorbidities that favor a high number of hospitalizations and longer hospital stays.
Keywords: VIH; Infecciones asociadas a la atención en salud; Paraguay